((x+16)(x+16))-5=0

Simple and best practice solution for ((x+16)(x+16))-5=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ((x+16)(x+16))-5=0 equation:


Simplifying
((x + 16)(x + 16)) + -5 = 0

Reorder the terms:
((16 + x)(x + 16)) + -5 = 0

Reorder the terms:
((16 + x)(16 + x)) + -5 = 0

Multiply (16 + x) * (16 + x)
((16(16 + x) + x(16 + x))) + -5 = 0
(((16 * 16 + x * 16) + x(16 + x))) + -5 = 0
(((256 + 16x) + x(16 + x))) + -5 = 0
((256 + 16x + (16 * x + x * x))) + -5 = 0
((256 + 16x + (16x + x2))) + -5 = 0

Combine like terms: 16x + 16x = 32x
((256 + 32x + x2)) + -5 = 0
(256 + 32x + x2) + -5 = 0

Remove parenthesis around (256 + 32x + x2)
256 + 32x + x2 + -5 = 0

Reorder the terms:
256 + -5 + 32x + x2 = 0

Combine like terms: 256 + -5 = 251
251 + 32x + x2 = 0

Solving
251 + 32x + x2 = 0

Solving for variable 'x'.

Begin completing the square.

Move the constant term to the right:

Add '-251' to each side of the equation.
251 + 32x + -251 + x2 = 0 + -251

Reorder the terms:
251 + -251 + 32x + x2 = 0 + -251

Combine like terms: 251 + -251 = 0
0 + 32x + x2 = 0 + -251
32x + x2 = 0 + -251

Combine like terms: 0 + -251 = -251
32x + x2 = -251

The x term is 32x.  Take half its coefficient (16).
Square it (256) and add it to both sides.

Add '256' to each side of the equation.
32x + 256 + x2 = -251 + 256

Reorder the terms:
256 + 32x + x2 = -251 + 256

Combine like terms: -251 + 256 = 5
256 + 32x + x2 = 5

Factor a perfect square on the left side:
(x + 16)(x + 16) = 5

Calculate the square root of the right side: 2.236067978

Break this problem into two subproblems by setting 
(x + 16) equal to 2.236067978 and -2.236067978.

Subproblem 1

x + 16 = 2.236067978 Simplifying x + 16 = 2.236067978 Reorder the terms: 16 + x = 2.236067978 Solving 16 + x = 2.236067978 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + x = 2.236067978 + -16 Combine like terms: 16 + -16 = 0 0 + x = 2.236067978 + -16 x = 2.236067978 + -16 Combine like terms: 2.236067978 + -16 = -13.763932022 x = -13.763932022 Simplifying x = -13.763932022

Subproblem 2

x + 16 = -2.236067978 Simplifying x + 16 = -2.236067978 Reorder the terms: 16 + x = -2.236067978 Solving 16 + x = -2.236067978 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + x = -2.236067978 + -16 Combine like terms: 16 + -16 = 0 0 + x = -2.236067978 + -16 x = -2.236067978 + -16 Combine like terms: -2.236067978 + -16 = -18.236067978 x = -18.236067978 Simplifying x = -18.236067978

Solution

The solution to the problem is based on the solutions from the subproblems. x = {-13.763932022, -18.236067978}

See similar equations:

| 70m^2-73m-35= | | 48m^2-119m-24= | | 7t^2-39t-70= | | 8x^3-4x^2-10x-3=0 | | 5t^2-19t-30= | | 3(b+1)=5(b-5)-6b | | 6x^2-17x+5= | | -6x-23=3x+13 | | 6x^2-25x+14= | | (8t+30)+(-2t-160)=-22 | | 0.7x-3.9=0.3 | | 0.50x+0.45(70)=45.5 | | 2x+12=-x+6 | | 3c^2-8c+5= | | 32x=12 | | .75x-.50=-2 | | 2s^2+7s+5= | | 16b^2+48b+27= | | 20=-5(4x+3)+21x | | 2(x-9)-(1+7x)=-6x | | 5-0.7k=5 | | 9x^2-17x-2= | | 5m^2+13m+10= | | 10x^2-17x+3= | | -2(w+6)-6=4(w+3) | | 2a^2+9a+9= | | 7x+3x=9x-4 | | -5.1d+4.9-(2d+0.4)+2.8d= | | 6x^2+23x-18= | | 167+19c-16=1132 | | y=0.6(x-3)(x-9) | | 0.6(x-3)(x-9)= |

Equations solver categories